Domain decomposition methods for the numerical solution of partial differential equations - Mathew, Tarek P. A. (Tarek Poonithara Abraham) (Lecture notes in computational science and engineering ;, 2008)
Domain decomposition methods are divide and conquer computational methods for the parallel solution of partial differential equations of elliptic or parabolic type. The methodology includes iterative algorithms, and techniques for non-matching grid discretizations and heterogeneous approximations. This book serves as a matrix oriented introduction to domain decomposition methodology. The topics discussed include hybrid formulations, Schwarz, substructuring and Lagrange multiplier methods for elliptic equations, computational issues, least squares-control methods, multilevel methods, non-self a.